Optical tomography system for process measurement using light-emitting diodes as a light source - Abdul Rahim, Ruzairi; Chan, K. S. (Society of Photo-Optical Instrumentation Engineers, 2004)
We describe the development of a tomographic system by employing low-cost optical sensors. This sensor selection aims at producing a low-cost solution in visualizing a low dense solid particle conveyor system. The final aim of this project is to achieve real-time monitoring of solid particles having low concentration flow when being conveyed in a vertical pneumatic conveyor. The developed tomography system consists of 32 pairs of light-emitting diodes (LEDs) and silicon PIN photodiodes. These sensors are used to monitor the emitted radiation for fluctuations caused by particles interfering with the beam when passing through it. Each sensor output depends on the position of flow regime within the sensing zone. The relationships between the particle distribution and light attenuation effects are investigated by reconstructing the cross-sectional image through computer programming. A data acquisition system is used to digitalize analog signals from the sensor system and is manipulated by a personal computer in real-time mode. The results obtained from this investigation show that low-cost optical sensors are suitable for monitoring low and medium concentration flowing materials.